Unraveling the determinants of microRNA mediated regulation using a massively parallel reporter assay - Ilya Vainberg Slutskin (Nature Portfolio, 2018)
MiRNAs are known regulators of gene expression. Here the authors perform a large-scale massively parallel reporter assay to investigate the effect of a large number of designed 3′ UTR sequences on reporter expression and asses how miRNA regulatory elements features affect miRNA mediated repression.